Human Rights or Private Rights? – Effective Protection of Victims in Global Supply Chains - Carsten Koenig (AJIL Unbound)
The business and human rights movement has made significant gains recently. After years of struggle, courts are increasingly embracing the idea of holding multinational corporations accountable for human rights abuses and environmental damage in countries of the Global South. Legislators are supplementing this with supply chain laws that impose due diligence obligations on multinationals, often backed by administrative sanctions. Civil liability for damages is less often provided, but hailed as a particular achievement in terms of the protection of victims. However, a closer look at civil liability in recent supply chain legislation adopted in Europe raises the question of whether the hallmark of such liability may actually be its greatest weakness. Supply chain liability is regularly linked to the breach of a due diligence obligation in relation to human rights abuses or environmental damage. This is typically based on international conventions that were not written for corporations and are difficult to apply in individual cases. In contrast, this essay argues that it is better to link supply chain liability to a violation of private rights, such as personal injury or property damage. This fits better with existing tort systems and ultimately benefits victims. The hallmark of supply chain liability should not be the link to human rights, but the establishment of duties of care across legal entities.